LITERATURE REVIEW: FACTORS INFLUENCING ONLINE COMPULSIVE BUYING - Pujianto, Jeanne Francoise Cen; Septiari, Elisabet Dita (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
This study is a descriptive study with a qualitative approach. The data of this study are literature studies related to “online compulsive buying.” The purpose of this study is to find out what factors influence online compulsive buying. Online compulsive buying is an important issue nowadays. It is because the rapid growth of the internet, followed by social media and e-commerce, has changed consumer buying behavior. The concept of buying before was to come to the store, choose, and pay with physical money; now, just press the smartphone, and it arrives at home. This convenience can satisfy consumers so that they will use it continuously. Online buying behavior will worsen if the consumer’s psychological condition is not good. It is called online compulsive buying. Then, this study was conducted to find. This study uses a literature review method with a systematic approach to explain the factors that influence and create online compulsive buying behavior. Several factors influence online compulsive buying: hypersensitive narcissism, anxiety sensitivity, social networking type, urge of online buying shopping and using social networks after viewing posts of influencers, material values scale (MVS), trier inventory for chronic stress (TICS), Barratt impulsiveness scale-15 (BIS-15), performance expectancy, effort expectancy, social influence, facilitating condition, stimulus - online platform characteristics, scarcity, online buying intention, online impulsive buying behavior, upward social comparison on social network sites, materialism, envy, gender, age, smartphone addiction, mood regulation, smartphone use, flow experience, online compulsive buying, online and offline compulsive buying behavior, distress, economic position, and income. Understanding online compulsive buying is important to understand factors that influence online compulsive buying, and to help consumers make effective interventions to prevent this negative behavior.